Controlled foam generation using cyclic diphasic flows through a constriction. (November 2017) - Gaillard, T.; Roché, M.; Honorez, C.; Jumeau, M.; Balan, A.; Jedrzejczyk, C.; Drenckhan, W.
Highlights: Detailed analysis of the properties of foams obtained by cyclic gas/liquid flow through a constriction. In-depth characterisation of the bubble size distributions showing their independence of the device parameters and their dependence on the formulation of the foaming solution. Demonstration of a hitherto unreported mechanism which produces reliably micron-sized bubbles with high monodispersity. High-speed imaging of the foaming process. Abstract: Numerous industrial and academic applications of liquid foams require a fine control over their bubble size distribution and their liquid content. A particular challenge remains the generation of foams with very small bubbles and low liquid content. A simple technique which fulfils these different criteria, the "double-syringe technique", has been exploited for decades in hospital applications. In this technique, the foaming liquid and gas are pushed repeatedly back and forth through the constriction that connects two syringes. After having motorised the technique we investigate here the influence of the different processing conditions on the obtained foam properties in a quantitative manner. We show that this technique is unique in producing foams with the same characteristic bubble size distributions over a wide range of processing conditions (tubing, fluid velocities, ...), making it an ideal tool for controlled foam generation. In contrast to other techniques, the liquid fraction in the double-syringe technique can be varied without impacting the bubble size distribution. Using high-speed imaging we show that bubbles are dispersed in the aqueous phase at two different places in the device via a hitherto unreported fragmentation mechanism. We put in evidence that the obtained bubble size distributions are largely independent of most processing parameters with the exception of the geometry of the constriction and the foam formulation. We put forward a first analysis of the non-dimensional numbers of the flow and compare our results with bubbles size distributions obtained from fragmentation processes. Future work on simplified model systems is required to explain the observed mechanisms.